Recent studies of synthetic antibody-based 3-MCPD determination technology - Hasim MUNAWAR; Prima LUNA; Irma KRESNAWATY; Happy WIDIASTUTI (Menara Perkebunan, 2021)
3-Chloro-1,2-propanediol (3-MCPD) is classified by the International Agency for Research on Cancer as carcinogenic material. 3-MCPD will also become one of the European Union's requirements, proposing the maximum level of the 3-MCPD in palm oil until 2.5 ppm. Although the reported technologies GCMS and HPLC-FLD demonstrated high sensitivity and selectivity on 3-MCPD determination, those technologies invest in chemical and time-consuming sample preparation and analysis. Molecularly imprinted polymer (MIP), or a synthetic antibody, can be used to recognize 3-MCPD. MIP is more robust under extreme environments such as temperature and pH. This paper, therefore, aims to discuss the application of MIP on sample extraction and analysis to detect 3-MCPD. MIP is synthesized by polymerization of functional monomers surrounding 3-MCPD as a template. 3-MCPD is then removed from the MIP, leaving active cavities. Thus, these sites can either covalently or non-covalently rebind to 3-MCPD. Computational or empirical studies could investigate the composition of MIP. MIP can be manufactured as MIP-based solid phase extraction (MIPSPE) and MIP-based sensor. Both applications showed significant analytical parameters, such as recovery higher than 90% and detection limit lower than 2.5 ppm.  Therefore, the application of MIP can be flexible for sample preparation and analysis on the 3-MCPD determination. MIP-based technology would be a prospective instrument to detect 3-MCPD.  In the future, producing MIP on an industrial scale will be a challenge to monitor the 3-MCPD level in palm oil.